2012
DOI: 10.3892/or.2012.2035
|View full text |Cite
|
Sign up to set email alerts
|

Swainsonine inhibits growth and potentiates the cytotoxic effect of paclitaxel in hepatocellular carcinoma in vitro and in vivo

Abstract: Abstract. Swainsonine, an extract from Astragalus membranaceus, exhibits broad inhibition of growth and pro-apoptotic activity in a number of tumor types. However, the underlying mechanism involved remains unclear. To investigate the effects and mechanisms of swainsonine on hepatocellular carcinoma (HCC), we performed experiments on HepG2, SMCC7721, Huh7 and MHCC97-H human hepatoma and HL-7702 human hepatocyte cells. We observed that swainsonine significantly inhibited the viability of human hepatoma cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…24 We previously found CD133 and EpCAM are useful markers for Huh-7 subpopulations, and the CD133 − /EpCAM − Huh-7 subpopulation possesses a profound invasive ability comparing with their DP counterparts. 17 In the supplementary data, we showed that three highly metastatic hepatoma cell lines, SMCC-7721, MHCC-97H and MHCC-97L, from the Shanghai region, 5,25 were all CD133-negative and EpCAM-negative by flow cytometric analysis (supplementary Figure 1). These DN hepatoma cell lines express high levels of Gli2 and MMP-1/2 (60-155-fold increase) compared with unsorted Huh-7 cells (supplementary Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…24 We previously found CD133 and EpCAM are useful markers for Huh-7 subpopulations, and the CD133 − /EpCAM − Huh-7 subpopulation possesses a profound invasive ability comparing with their DP counterparts. 17 In the supplementary data, we showed that three highly metastatic hepatoma cell lines, SMCC-7721, MHCC-97H and MHCC-97L, from the Shanghai region, 5,25 were all CD133-negative and EpCAM-negative by flow cytometric analysis (supplementary Figure 1). These DN hepatoma cell lines express high levels of Gli2 and MMP-1/2 (60-155-fold increase) compared with unsorted Huh-7 cells (supplementary Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Astragalus membranaceus (AM) and Salvia miltiorrhiza (SM), commonly used Chinese medicinal plants, have been shown to be effective in suppressing hepatocarcinogenesis in rats and in human, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] but the mechanism is unclear. Transforming growth factor-β (TGF-β), especially the TGF-β1 isoform, is known to be the critical profibrotic cytokine involved in hepatocellular carcinoma (HCC) development.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that SW enhances apoptosis in MHCC97-H cells, colorectal cancer cells, and human diffuse large B cell lymphoma (Suzuki and Abe, 2008;deFreitas-Junior et al, 2012;You et al, 2012). By upregulating Bax and downregulating Bcl-2, SW promotes apoptosis through activation of the mitochondrial pathway (Li et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%